Pharmacy Workload and Workforce Requirements at MOH Hospitals during Ten years Mass Gathering Hajj (2006-2015) in Makkah Region, Saudi Arabia - Alomi, Yousef Ahmed; Alhennawi, Khairat; Khayayt, Nizar (Journal of Pharmacy Practice and Community Medicine)
Purpose: To explore the pharmaceutical care services workload analysis and human resources requirements at Ministry of Health Hospitals during mass gathering Hajj ten years (2006-2015), Saudi Arabia. Methods: It is a retrospective of ten years (2006-2015) of hospital pharmacies workload during mass gathering Hajj period. The duration of workload collection was 15 days. The pharmacists provide pharmaceutical to all patients either Pilgrim or not Pilgrim at Makkah region. It included Mona holy places hospitals; Arafa holy places hospitals, and Makkah city. The workforce requirements calculated based on MOH workforce standards per bed and the workload drives as central pharmacy services, patient specific pharmacy activities, and general administration specific pharmacy activities. Results: The total number of Pilgrims (1,952,817 3,161,573) with average of (2,445,208). The total number of prescriptions (99,886-257,545) with average (180,120), it represented (5.11-12.07%) with average (7.86%) of all pilgrims. The average number of pharmacist needed (9.49 FTE) for inpatient services per hospital, (48.85 FTE) for Emergency services per hospital, and (21.85 FTE) for Ambulatory care services per hospital. The average number of pharmacist based on Ministry of Health standards calculation per hospital was (37.1 FTE), while the mean number pharmacist needed to base on workload for all services was (80.19 FTE) per hospital. It is (2.16 fold) more incremental than MOH pharmacist workforce standards per bed. There were not any central pharmacy activities, and clinical pharmacy services or administrative pharmacy activities. Conclusion: The Workload analysis of pharmaceutical care services as a part of TQM indicators during mass gathering Hajj. Clinical pharmacy activities missed with emphasis on patient-specific clinical pharmacy. There is a high demand for pharmacists’ workforce during mass gathering Hajj period in Makkah Region, Saudi Arabia.
Keywords: Pharmacy; Workload; Workforces; Mass Gathering; Hajj; Makkah; Ministry of Health; Saudi Arabia